STUDI EKOLOGI MATERIAL PEMBENTUK RUANG TERBUKA PADA RUMAH TINGGAL - Waisnawa, I Made Jayadi (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2019)
Traditional Hindu societies in particular, have thought and applied concepts related to the harmony of relations between humans and nature. In each application, these concepts always consider nature and all its contents for the balance of ecological harmony. This concept has basically been applied by traditional Hindu societies in Bali however, the understanding of the ecology in Hinduism is now being ignored. Especially in the area of ​​Bali, this condition is found mostly in residential areas that are densely populated, one of which is the residential environment of Bumi Dalung Permai. Anticipating and getting around the limitations of land the government has issued regulations related to the Building Basic Coefficient and Green Open Space . This study aims to determine the community's understanding of the importance of open space and ecology in relation to material applications. This study uses qualitative methods with descriptive explanations. Primary data is obtained through the distribution of questionnaires in several houses that have been adjusted to the research criteria. Data collection uses purposive sample method, with several criteria such as the breadth of space, existence ofopen space and located in the residential area of ​​Bumi Dalung Permai. Based on the data obtained, open space in the residential area is dominated by the application of pavement material (cement, paving, natural stone and ceramics. Open space in the living room has several functions such as garage, drying area, cleaning area and garden.